BRAFV600E mutation in fine‐needle aspiration aspirates: Association with poorer prognostic factors in larger papillary thyroid carcinomas. Issue 4 (7th April 2012) - Lee, Ji In; Jang, Hye Won; Kim, Sun Wook; Kim, Jong–Won; Oh, Young Lyun; Chung, Jae Hoon
Abstract Background Recent studies have shown that BRAFV600E mutation is associated with poor prognostic factors in papillary thyroid carcinoma (PTC). However, there are no studies about the association of the BRAFV600E mutation with poor prognostic factors according to tumor size in PTC. Methods We investigated the prevalence of the BRAFV600E mutation and its association with prognostic factors according to tumor size of PTC. BRAFV600E mutation status was assessed in thyroid fine‐needle aspiration (FNA) specimens from 605 patients before thyroidectomy for PTC, and its association with postoperative clinicopathologic factors was evaluated. Results The overall prevalence of the BRAFV600E mutation was 67%, and larger tumors more often had the BRAFV600E mutation (p for trend < .05). The BRAFV600E mutation was significantly associated with male sex, tumor size, extrathyroidal invasion, nodal metastasis, and advanced tumor stage (p < .05). There was a significant size‐dependent relationship between the presence of the BRAFV600E mutation and extrathyroidal invasion, nodal metastasis, and advanced tumor stage (p for trend < .05). Conclusion The prevalence of the BRAFV600E mutation increased with increased tumor size. Preoperative FNA‐detected BRAFV600E mutation was associated with poor prognostic factors, and the association was stronger in larger tumors. © 2012 Wiley Periodicals, Inc. Head Neck, 2013